1974
DOI: 10.1083/jcb.62.3.717
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Study of Microsomes and Isolated Subcellular Membranes From Rat Liver

Abstract: lsopycnic equilibration and sedimentation rate studies of rat liver microsomes led previously to the assignment of microsomal constituents into group al (monoamine oxidase), group a2 (5'-nucleotidase, alkaline phosphodiesterase I, alkaline phosphatase and cholesterol), group a3 (galactosyltransferase), group b (NADH cytochrome ¢ reductase, NADPH cytochrome c reductase, aminopyrine demethylase, cytochrome b5 and P 450), and group c (glucose 6-phosphatase, esterase, nucleoside diphosphatase, 13-glucuronidase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
112
2

Year Published

1974
1974
2004
2004

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(122 citation statements)
references
References 32 publications
8
112
2
Order By: Relevance
“…These results are doubly meaningful, in that they show that the bulk of the microsomal cholesterol is physically independent from the structures bearing group b and ¢ enzymes, and also that the latter structures do not contain appreciable amounts of cholesterol per unit weight, at least in a form accessible to digitonin binding. Our conclusion, which is at variance with the views of other authors (13,23), will be further supported in the next paper of this series (5). The intracellular localization of cholesterol is examined below.…”
Section: Distribution Of Chemical Constituentscontrasting
confidence: 50%
See 2 more Smart Citations
“…These results are doubly meaningful, in that they show that the bulk of the microsomal cholesterol is physically independent from the structures bearing group b and ¢ enzymes, and also that the latter structures do not contain appreciable amounts of cholesterol per unit weight, at least in a form accessible to digitonin binding. Our conclusion, which is at variance with the views of other authors (13,23), will be further supported in the next paper of this series (5). The intracellular localization of cholesterol is examined below.…”
Section: Distribution Of Chemical Constituentscontrasting
confidence: 50%
“…Thus it is obvious that the rougher parts of the endoplasmic reticulum (ER) are essentially free of cholesterol. This conclusion may be extended to the remainder of the ER in view of the results of experiments (5,40) which have shown that previous treatment of the microsomes with small amounts of digitonin causes a considerable shift to higher densities of the distribution patterns of cholesterol and of some group a enzymes, without at all affecting those of group b and c enzymes. These results are doubly meaningful, in that they show that the bulk of the microsomal cholesterol is physically independent from the structures bearing group b and ¢ enzymes, and also that the latter structures do not contain appreciable amounts of cholesterol per unit weight, at least in a form accessible to digitonin binding.…”
Section: Distribution Of Chemical Constituentsmentioning
confidence: 98%
See 1 more Smart Citation
“…The faster moving band of the cytochrome b~ and heme preparations showed a green-yellow color, and did not bind the dye. resuspended in a 43.1% sucrose solution, z To increase the equilibrium density of contamination fragments of plasma membranes, digitonin was added in an amount equivalent to 0.135 mg/g fresh weight of liver originally homogenized (3). This and all subsequent sucrose solutions contained 3 mM imidazole-HC1 buffer, pH 7.4.…”
Section: Preparation Of Subcellular Membrane Fractionsmentioning
confidence: 99%
“…Although different membranes may be functionally related, they have been shown to be biochemically distinguishable entities in various systems [1][2][3][4]. Some enzymes, however, have been demonstrated to be localized in more than one type of membrane.…”
Section: Introductionmentioning
confidence: 99%